39. CLINICAL EPIDEMIOLOGY AND ASSOCIATED FACTORS OF RECURRENT PNEUMONIA IN CHILDREN (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to investigate the clinical epidemiological characteristics and identify factors associated with the recurrence frequency of pneumonia in children.Methods: A cross-sectional descriptive study was conducted on 150 children diagnosed with recurrent pneumonia from October 2023 to September 2024 at the Outpatient and Voluntary Treatment Department of Nghe An Obstetrics and Pediatrics Hospital. The study analyzed the relationship between various factors and the recurrence frequency of pneumonia.Results: The prevalence of recurrent pneumonia was 8.0%. The majority of cases were in children aged 2–12 months, accounting for 44.7%. The incidence was higher in males than females, with a male-to-female ratio of 1.78. The most common recurrence frequency was three episodes (34.7%), with an average of 3.13 ± 1.21 episodes. The etiological agents identified in recurrent pneumonia episodes included Haemophilus influenzae (6.0%), Streptococcus pneumoniae (10.0%), Mycoplasma pneumoniae (4.0%), RSV virus (11.0%), influenza virus (3.0%), while 66.0% of cases had no identifiable causative pathogen. Recurrent pneumonia occurring more than four times was significantly associated with a history of personal allergies (p
Keywords: Recurrent pneumonia; epidemiology; associated factors